The aftermath of enforced disappearance and concealment.: A qualitative inquiry with families in Paine, Chile - Morales-Sáez , Nicolás; Espina, Joel (Torture Journal, 2021)
Introduction: The forced disappearance of peasants in the Paine commune, Chile, dates back to the first months after the coup in 1973. Ten years ago, as a result of a judicial investigation, the location of a mass grave was revealed to more than one hundred kilometers from the detention site. This finding allowed the identification of eleven detainees who disappeared by genetic methods, along with another five recognized from forensic archaeological evidence. Our main objective is to account for the aftermath of forced disappearance and the operation to conceal the bodies of three generations of relatives of disappeared detainees. Methods: Qualitative research: Case study, carried out between 2014 and 2015, with a total of 19 interviewees from three generations, belonging to six families from Paine. Semi-structured interviews were conducted, with two to three sessions per interviewee and three discussion groups, one for each generation. Results: The three generations face in a dissimilar way the slogan of where are they ?, as well as they attribute different meanings to the skeletal remains. It contrasts the "duty to recognize" of the first generation with the interpellation of the third generation through practices that vindicate the collective dimension of mourning. In the experiences of intergenerational dialogue, spaces of memory have taken center stage, in particular the location of the common grave. One of the relevant results of this investigation has been to give an account of the social experience of forensic identification. Conclusions: Family relationships do not convey an integrating story but rather what stands out is the emptiness of representation and intergenerational silences. Science, through DNA, offers statistical evidence of identification, but the decision is maintained in the individual jurisdiction of each family member. Comprehensive forensic work with the participation of archaeologists, anthropologists, dentists and other experts contributes to restoring the dignity of the victimized body.